KEDUDUKAN BANK SEBAGAI KREDITOR SEPARATIS DALAM PENGURUSAN DAN PEMBERESAN HARTA PAILIT - Yane Pakel (Al-Amwal : Journal of Islamic Economic Law, 2018)
There are two purpose of this research 1) to know and analyze banks role as secured creditor in executing collaterals. This is cause by the uncertainty of the execution rights as a result of the inconsistencies of regulations mention to Article 55, Article 56 and Article 59 of The Republic of Indonesia Number 37 of 2004 regarding Bankruptcy and Suspension of Payment Obligation. 2) to know and examine the legal protection for secure banks in bankruptcy settlement. This research is a normative legal research that is supported by interview. Secondary data is taken from primary, secondary and tertiary legal resource. Data collection method is documentary study and library research. Data analysis is a qualitative analysis.Based on the result and discussion, bank as a secured creditor has the right to execute collateral that is pledged by debtor, as if bankruptcy does not take place (pursuant to Article 55 paragraph 1)The bankruptcy law has ruled the creditors right on the collateral, but there is uncertainty of execution right. This is caused by the inconsistency of regulations of Article 55, Article 56 and Article 59 of The Republic of Indonesia Number 37 of 2004 regarding Bankruptcy and Suspension of Payment Obligation. Article 56 and Article 59 are limit the creditors rights. The current law does not strongly enforced, thus the bank is seeking right by auction or hidden transaction